27. THE DISEASE STRUCTURE AND ASOCIATED FACTORS AMONG ELDERLY HOSPITALIZED IN MY DUC DISTRIC GENERAL HOSPITAL, HANOI IN 2024 (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the disease structure among inpatient elderly at My Duc district General Hospital, Hanoi in 2024, and to identify associated factors.Subject and methods: The study used medical record data of elderly patients (aged ≥ 60 years) who were hospitalized at My Duc district General Hospital from January 1, 2024 to December 31, 2024. The study design is descriptive retrospective study.Results: In 2024, non-communicable diseases accounted for the highest proportion (77.6%) of all inpatient cases, followed by communicable diseases at 18.8%, and injuries, poisoning, and external causes at the lowest proportion of 3.6%. Among the ICD-10 chapters, diseases of the respiratory system (chapter X) had the highest prevalence (20%), followed by diseases of the musculoskeletal system and connective tissue (chapter XIII) at 17%, diseases of the nervous system (chapter VI) and diseases of the digestive system (chapter XI), both at 10%. Factors associated with an increased risk of non-communicable diseases included age ≥ 80 years and urban residence. Factors associated with a higher likelihood of communicable diseases included rural residence and admission during the period from June to November. Risk factors for injuries, poisoning, and external causes included age ≥ 80 years and having health insurance coverage.Conclusions: Hospitalized elderly patients at My Duc district General Hospital were predominantly diagnosed with non-communicable diseases. Significant factors associated with non-communicable diseases included age ≥ 80 years and living in urban areas.
Keywords: Diseases structure, disease pattern, elderly patients, inpatient treatment.